Overview of the Quality of Life of Families Accompanying Cancer Patients in the Oncology Room - Larasati, Anastasia Diah (Indonesian Journal of Global Health Research, 2024)
Cancer is a term used for cellular growth disorders that fail to control cell proliferation and maturation. Patients need to be accompanied by family during the cancer recovery treatment process. Families have a big role in accompanying family members who are undergoing cancer treatment in hospitals, starting from physical, psychological, spiritual and economic assistance. The aim of this research is to understand the quality of life of families accompanying cancer patients in the oncology room at RSD KRMT Wongsonegoro. This research is an analytical descriptive study, using the WHOQOL BREF questionnaire, with a sample size of 40 respondents. This research uses frequency distribution test by SPSS 16. The results found are The quality of life of families accompanying patients with cancer using the WHO QOL BREF instrument is in the medium range with 26 people (65%), and good quality of life is 3 people (7.5%).